Adhesive sheet and dicing-die bonding film

By using thermally expandable microspheres and appropriate resin layers in the adhesive sheet, the problem of the conventional adhesive sheet hindering expansion properties and breakage during peeling in the semiconductor chip expansion process is solved, and good peelability and expansion properties are achieved.

CN119463719APending Publication Date: 2025-02-18NITTO DENKO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411072726.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-08
Filing Date
2024-08-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The conventional adhesive sheet can easily hinder the expansion of the adherend during the expansion process of the semiconductor chip, and may cause damage to the semiconductor chip during peeling.

Method used

Adhesive layer containing thermally expandable microspheres are used to reduce the adhesive force by expansion of thermally expandable microspheres, thereby achieving good peeling properties, while using a resin layer with an appropriate glass transition temperature to optimize stress transfer and expansion properties.

Benefits of technology

It achieves an adhesive sheet with excellent smoothness and high position accuracy without hindering the expansion of the adherend and avoids damage to the semiconductor chip during peeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463719A_ABST
    Figure CN119463719A_ABST
Patent Text Reader

Abstract

The invention relates to an adhesive sheet and a dicing-die bonding film. Provided is an adhesive sheet which is capable of forming an adhesive layer having excellent smoothness despite including an adhesive layer containing thermally expandable microspheres, and which is not susceptible to impeding the expansibility of an adherend. A pressure-sensitive adhesive sheet according to an embodiment of the present invention comprises a base material, a resin layer, and a pressure-sensitive adhesive layer in this order, the pressure-sensitive adhesive layer containing thermally expandable microspheres, and the resin layer has a base polymer having a glass transition temperature (Tg) of-35 DEG C to 20 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The present invention relates to an adhesive sheet, and more particularly to an adhesive sheet that responds to thermal stimulation and exhibits easy peelability. Background Art In the past, adhesive sheets were sometimes used to fix or temporarily fix the workpiece when processing electronic components, etc. For example, adhesive sheets are sometimes used as temporary fixtures in an expansion process, and the expansion process is to cut off the semiconductor wafer with a fragile part together with the chip bonding film by stealth dicing when manufacturing semiconductor chips, so as to expand the interval between adjacent semiconductor chips. The adhesive sheet used in such a process is required not to hinder the smoothness of the bonding surface, the expandability of the semiconductor wafer (chip) and the chip bonding film. Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2003-201452 Summary of the invention The present invention has been made to solve the above-mentioned conventional technical problems, and its object is to provide a pressure-sensitive adhesive sheet which can form a pressure-sensitive adhesive layer having excellent smoothness and is less likely to inhibit the expansion of an adherend despite including a pressure-sensitive adhesive layer containing heat-expandable microspheres.

[0001] The pressure-sensitive adhesive sheet according to the embodiment of the present invention comprises: a substrate, a resin layer, and a pressure-sensitive adhesive layer in this order. The pressure-sensitive adhesive layer contains heat-expandable microspheres. The resin layer has a base polymer having a glass transition temperature Tg of -35°C to 20°C.

[0002] In the pressure-sensitive adhesive sheet described in [1] above, the resin layer may have a loss modulus E″ at -15°C of 10 MPa to 3000 MPa.

[0003] In the pressure-sensitive adhesive sheet described in [1] or [2], the resin layer may have a storage modulus E' at -15°C of 10 MPa to 2500 MPa.

[0004] In the pressure-sensitive adhesive sheet according to any one of [1] to [3] above, the resin layer may not be active energy ray-curable.

[0005] In the pressure-sensitive adhesive sheet according to any one of [1] to [4] above, the resin layer may have a thickness of 5 μm to 40 μm.

[0006] In the pressure-sensitive adhesive sheet described in any one of [1] to [5] above, the base polymer may have a structural unit (A1) derived from a monomer (A1), wherein the monomer (A1) has a glass transition temperature Tg of -20°C to 15°C when formed into a homopolymer, and the content of the structural unit (A1) is 50 parts by weight or more relative to 100 parts by weight of the base polymer.

[0007] In the pressure-sensitive adhesive sheet of [6] above, the base polymer may be an acrylic polymer, and the monomer (A1) may be ethyl acrylate, methyl acrylate, or 2-ethylhexyl methacrylate.

[0008] In the pressure-sensitive adhesive sheet described in any one of [1] to [7] above, the base polymer may have a structural unit (B1) derived from a monomer (B1), wherein the monomer (B1) has a glass transition temperature Tg of 100°C to 175°C when formed into a homopolymer, and the content of the structural unit (B1) is 40 parts by weight or less relative to 100 parts by weight of the base polymer.

[0009] In the pressure-sensitive adhesive sheet described in any one of [1] to [8] above, the monomer (B1) may be methyl methacrylate, N-acryloylmorpholine, N-vinyl-2-pyrrolidone, or N-phenylmaleimide.

[0010] In the pressure-sensitive adhesive sheet according to any one of [1] to [9] above, the pressure-sensitive adhesive layer may have a thickness of 5 μm to 40 μm.

[0011] In the pressure-sensitive adhesive sheet described in any one of [1] to

[10] above, the pressure-sensitive adhesive layer may have a light absorptivity of 25% to 100% at a wavelength of 900 nm.

[0012] In the pressure-sensitive adhesive sheet according to any one of [1] to

[11] above, the substrate may include a polyolefin-based resin.

[0013] In the pressure-sensitive adhesive sheet according to any one of [1] to

[12] above, the substrate may include a layer formed of a polyolefin-based resin layer and a layer formed of an ethylene-vinyl acetate copolymer-based resin.

[0014] The dicing die-bonding film according to the embodiment of the present invention includes the adhesive sheet according to any one of [1] to

[13] above and a die attach film. Effects of the Invention According to the present invention, there can be provided a PSA sheet which can form a PSA layer having excellent smoothness and is less likely to inhibit the expansion of an adherend despite including a PSA layer containing heat-expandable microspheres. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1This is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. Figure 2 This is a schematic cross-sectional view of a dicing die bonding film according to one embodiment of the present invention. Description of Reference Numerals 10: substrate; 20: resin layer; 30: adhesive layer; 40: die attach film; 100: adhesive sheet; 200: dicing-die bonding film. DETAILED DESCRIPTION A. Overview of PSA Sheets Figure 1 It is a schematic cross-sectional view of an adhesive sheet of an embodiment of the present invention. The adhesive sheet 100 comprises: a substrate 10, a resin layer 20 and an adhesive layer 30 in sequence. The adhesive layer comprises heat-expandable microspheres. As long as the effect of the present invention can be obtained, the adhesive sheet may also have any other appropriate layers. For example, other adhesive layers may also be provided on the side of the substrate opposite to the stress transfer layer. The above-mentioned heat-expandable microspheres can be foamed at a specified temperature. With regard to the adhesive layer comprising such heat-expandable microspheres, the heat-expandable microspheres are foamed due to heating, thereby producing concavo-convex on the adhesive surface (i.e., the adhesive layer surface), and the adhesive force is reduced or disappears. When the adhesive sheet of the present invention is used as a temporary fixing sheet for a processed object, for example, when processing electronic components (such as semiconductor chips), the adhesive sheet is used as a temporary fixing sheet for a processed object, and when the processed object is subjected to a specified processing (such as the expansion of the adherend), the adhesive force required for temporary fixing is embodied, and when the processed object is peeled off after processing, the adhesive force is reduced or disappears by heating, and good peelability is embodied. It should be noted that, as the above-mentioned heating, for example, heating by raising the ambient temperature, heating by causing the adhesive layer to absorb laser, etc. can be cited. Along with the miniaturization, thinning of semiconductor package in recent years, the ratio of functional layer relative to semiconductor chip increases, and as a result, there is a tendency of fragility in semiconductor chip. In the case of using the previous curable adhesive sheet in the temporary fixation of such semiconductor chip, the problem of the semiconductor chip destruction when peeling is generated. On the other hand, the above-mentioned adhesive sheet possessing the adhesive layer comprising heat-expandable microspheres embodies peelability as described above, and is therefore useful to the temporary fixation of fragile semiconductor chip, and if the above-mentioned adhesive sheet is used, the semiconductor chip can be prevented from being destroyed and the peeling operation is performed. The resin layer includes a base polymer having a glass transition temperature Tg of -35°C to 20°C. Such a resin layer can be a stress transfer layer that can preferably transfer stress to the adherend (e.g., semiconductor chip / chip bonding film laminate) when stretched (i.e., expanded) in a state where the adherend is attached. The adhesive sheet can be preferably used as a temporary fixture in an expansion process, for example, in which the semiconductor wafer with a fragile portion is cut together with the chip bonding film by stealth cutting or the like when manufacturing semiconductor chips, thereby expanding the interval between adjacent semiconductor chips. In an embodiment of the present invention, by providing the resin layer, even if the thickness of the adhesive layer is thickened, the stress relaxation of the adhesive sheet during expansion can be suppressed, and the adherend can be fully stretched. Therefore, if the adhesive sheet is used in the expansion process when manufacturing semiconductor chips, the semiconductor wafer can be preferably cut, and as described above, due to the action of the heat-expandable microspheres, the semiconductor chip obtained by cutting can be preferably peeled off. In embodiments of the present invention, even if thickening adhesive layer can also play stress transmission ability, although therefore comprising heat-expandable microspheres, also can form the adhesive layer of excellent surface smoothness (smoothness before heat-expandable microspheres foaming).By forming the adhesive layer of excellent surface smoothness, can obtain with the excellent adhesive sheet of the closeness of adherend.In addition, can provide a kind of adhesive sheet, this adhesive sheet can positional accuracy well keep the semiconductor chip obtained by cutting off.Semiconductor chip is more tiny, and above-mentioned effect becomes favourable effect more. The adhesive force at 23°C when the adhesive layer of the above-mentioned adhesive sheet is attached to polyethylene terephthalate is preferably 0.3N / 20mm or more, more preferably 0.5N / 20mm to 30N / 20mm, further preferably 0.5N / 20mm to 20N / 20mm, and further preferably 3.5N / 20mm to 15N / 20mm. If it is such a range, for example, an adhesive sheet useful as a temporary fixing sheet for manufacturing electronic components can be obtained. In this specification, the adhesive force refers to the adhesive force in a state where the adhesive force is not reduced due to the expansion of the heat-expandable microspheres, and refers to the adhesive force in a state where the thermal history of more than 40°C has not been passed. In addition, the adhesive force refers to the adhesive force measured by the method according to JIS Z 0237:2009 (lamination conditions: 2kg roller 1 reciprocating, peeling speed (stretching speed): 300mm / min, peeling angle 180°). The adhesive strength of the adhesive layer of the adhesive sheet when attached to polyethylene terephthalate is preferably reduced to 0.3 N / 20 mm or less (preferably 0.2 N / 20 mm or less, more preferably 0.1 N / 20 mm or less) by heating at a temperature of preferably 150°C to 300°C, more preferably 170°C to 280°C. The thickness of the pressure-sensitive adhesive sheet is preferably 10 μm to 400 μm, more preferably 20 μm to 200 μm, and even more preferably 30 μm to 150 μm. The storage modulus E' of the adhesive sheet at -15°C is preferably 200 MPa or more and 500 MPa or less. If it is within such a range, the cracking of the dicing tape can be suppressed, and the die bonding sheet can be cut well. The storage modulus E' of the dicing tape at -15°C is preferably 200 MPa or more, and more preferably 220 MPa or more. The larger the storage modulus E' at -15°C, the better the die bonding sheet can be cut. That is, better cutting performance can be exerted. The storage modulus E' at -15°C can be 500 MPa or less, or 400 MPa or less. The smaller the storage modulus, the further suppression of the cracking of the dicing tape. The storage modulus E' can be measured using a dynamic viscoelasticity measuring device (for example, the trade name "RSA-G2" manufactured by TA instruments) under the measuring conditions of a frequency of 1 Hz and a heating rate of 5°C / min. B. Resin layer The content of the base polymer in the resin layer is preferably 60% by weight or more, more preferably 70% by weight to 99% by weight, and even more preferably 80% by weight to 99% by weight. As described above, the resin layer is formed of a base polymer having a glass transition temperature Tg of -35°C to 20°C. The glass transition temperature of the base polymer constituting the resin layer is preferably -33°C to 18°C, more preferably -30°C to 15°C, further preferably -25°C to 13°C, more preferably -20°C to 10°C, and particularly preferably -15°C to 10°C. If it is within such a range, the above-mentioned effect is significant. In addition, when the glass transition temperature Tg of the base polymer is too low, the deformation during heating (for example, heating by laser irradiation) is large, which may cause positional displacement of the adherend. In addition, when the glass transition temperature Tg of the base polymer is too high, it may be easy to break during the expansion process. The glass transition temperature is obtained by the Fox calculation formula. The Fox calculation formula is as follows: The glass transition temperature Tg (°C) of the copolymer and the glass transition temperature Tg (°C) of the homopolymer obtained by homopolymerizing the monomers constituting the copolymer. i It should be noted that in the following Fox formula, Tg (°C) represents the glass transition temperature of the copolymer, W i represents the weight fraction of monomer i, Tg i (°C) represents the glass transition temperature of the homopolymer formed from monomer i. 1 / (273+Tg)=Σ(Wi / (273+Tg i )) As the glass transition temperature of a homopolymer, the value described in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999) can be used. In addition, when a plurality of Tg values ​​are described in this document, the "conventional" value is adopted. In one embodiment, the base polymer has a structural unit (A1) derived from a monomer (A1), and the glass transition temperature Tg of the monomer (A1) when made into a homopolymer is -20°C to 15°C. Monomer (A1) may be the main monomer constituting the base polymer. The content of the structural unit (A1) is preferably 50 parts by weight or more, more preferably 55 parts by weight or more relative to 100 parts by weight of the base polymer. If it is in such a range, an adhesive sheet with excellent stress transfer properties can be obtained. In addition, the content of the structural unit (A1) is, for example, 100 parts by weight or less relative to 100 parts by weight of the base polymer. In one embodiment, the content of the structural unit (A1) is 95 parts by weight or less relative to 100 parts by weight of the base polymer. The glass transition temperature Tg of the monomer (A1) (i.e., the main monomer) when it is made into a homopolymer is preferably -20°C to 10°C. When the homopolymer glass transition temperature Tg of the monomer (A1) is less than -20°C, the stress relaxation is too high, which may hinder the expansion of the adherend. In addition, when the homopolymer glass transition temperature Tg of the monomer (A1) is greater than 15°C, the adhesive sheet may break during expansion. The above-mentioned base polymer may also have a structural unit (B1) derived from a monomer (B1), and the glass transition temperature Tg of the monomer (B1) when made into a homopolymer is 100°C to 175°C. The content ratio of the structural unit (B1) is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, and further preferably 30 parts by weight or less relative to 100 parts by weight of the base polymer. If it is in such a range, an adhesive sheet that is not easy to break during expansion can be obtained. The content ratio of the structural unit (B1) is preferably 5 parts by weight or more relative to 100 parts by weight of the base polymer. If it is in such a range, an adhesive sheet with excellent stress transfer properties can be obtained. It should be noted that when a monomer having a glass transition temperature Tg greater than 175°C when made into a homopolymer is used, it is possible that the adhesive sheet breaks during expansion. Examples of the monomer (B1) include methyl methacrylate, N-acryloylmorpholine, N-vinyl-2-pyrrolidone, and N-phenylmaleimide. By using these monomers, a pressure-sensitive adhesive sheet having excellent stress transfer properties can be obtained. These monomers can be used alone or in combination of two or more. As the base polymer contained in the above-mentioned resin layer, any appropriate polymer can be used as long as the effect of the present invention can be obtained. In one embodiment, as the base polymer contained in the resin layer, an acrylic polymer (homopolymer or copolymer) is used. The acrylic polymer can be obtained by using one or more (meth) alkyl acrylates as monomer components. Specific examples of the alkyl (meth)acrylates include C1-20 alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among them, alkyl (meth)acrylates having a linear or branched alkyl group having 4 to 20 carbon atoms (more preferably 6 to 20, and particularly preferably 8 to 18) are preferred, and 2-ethylhexyl (meth)acrylate is more preferred. In one embodiment, as the alkyl (meth)acrylate, an alkyl (meth)acrylate having a glass transition temperature of -20°C to 15°C is used. In the acrylic polymer, "alkyl (meth)acrylate having a glass transition temperature of -20°C to 15°C may correspond to the above-mentioned "monomer (A1)". In this specification, for convenience, the alkyl (meth)acrylate having a glass transition temperature of -20°C to 15°C is referred to as "acrylic monomer (A1)". Examples of the acrylic monomer (A1) include ethyl acrylate, methyl acrylate, and 2-ethylhexyl methacrylate, among which ethyl acrylate and methyl acrylate are preferred. In the case where the acrylic polymer is a copolymer, the content of the structural unit derived from the acrylic monomer (A1) is preferably 50 parts by weight or more, more preferably 55 parts by weight or more, further preferably 60 parts by weight or more, and particularly preferably 70 parts by weight or more relative to 100 parts by weight of the base polymer. If it is such a range, an adhesive sheet with excellent stress transfer properties can be obtained. In addition, the content of the structural unit derived from the acrylic monomer (A1) is, for example, 95 parts by weight or less, preferably 90 parts by weight or less relative to 100 parts by weight of the base polymer. The glass transition temperature Tg of the acrylic monomer (A1) (i.e., the monomer containing 50 parts by weight or more) when it is made into a homopolymer is preferably -20°C to 10°C. When the homopolymer glass transition temperature Tg of the acrylic monomer (A1) is less than -20°C, the stress relaxation is high and the expansion of the adherend may be hindered. In addition, when the homopolymer glass transition temperature Tg of the acrylic monomer (A1) is greater than 15°C, the adhesive sheet may break during expansion. The acrylic polymer is intended to modify cohesion, heat resistance, crosslinking properties, etc., and may contain units corresponding to other monomers copolymerizable with the alkyl (meth)acrylate as required. Examples of such monomers include: carboxyl-containing monomers such as acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride monomers such as maleic anhydride and itaconic anhydride; hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl methacrylate; styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamide-2-methyl Sulfonic acid group-containing monomers such as (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-methylolpropane (meth)acrylamide, etc.; (meth)acrylic acid aminoalkyl ester monomers such as (meth)acrylic acid aminoethyl ester, (meth)acrylic acid N,N-dimethylaminoethyl ester, (meth)acrylic acid tert-butylaminoethyl ester; (meth)acrylic acid methoxyethyl ester, (meth)acrylic acid ) (Meth) acrylate alkoxyalkyl ester monomers such as ethoxyethyl acrylate; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide; N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide Succinimide monomers such as amine, N-(meth)acryloyl-8-oxyoctamethylene succinimide; vinyl monomers such as vinyl acetate, vinyl propionate, N-vinyl pyrrolidone, methyl vinyl pyrrolidone, vinyl pyridine, vinyl piperidone, vinyl pyrimidine, vinyl piperazine, vinyl pyrazine, vinyl pyrrole, vinyl imidazole, vinyl oxazole, vinyl morpholine, N-vinyl carboxylic acid amides, styrene, α-methyl styrene, N-vinyl caprolactam; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy-containing acrylic monomers such as glycidyl (meth)acrylate;N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, N-(meth)acryloylmorpholine and other monomers having a ring containing a nitrogen atom; polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate and other diol acrylate monomers; tetrahydrofurfuryl (meth)acrylate, fluoro(meth)acrylic acid ester, etc. Acrylate monomers having heterocyclic rings, halogen atoms, silicon atoms, etc., such as esters, silicone (meth) acrylates; polyfunctional monomers such as hexanediol di(meth) acrylate, (poly)ethylene glycol di(meth) acrylate, (poly)propylene glycol di(meth) acrylate, neopentyl glycol di(meth) acrylate, pentaerythritol di(meth) acrylate, trimethylolpropane tri(meth) acrylate, pentaerythritol tri(meth) acrylate, dipentaerythritol hexa(meth) acrylate, epoxy acrylate, polyester acrylate, and urethane acrylate; olefin monomers such as isoprene, butadiene, and isobutylene; vinyl ether monomers such as vinyl ether, etc. These monomers can be used alone or in combination of two or more. Among the above, carboxyl-containing monomers (especially preferably acrylic acid) or hydroxyl-containing monomers (especially preferably hydroxyethyl (meth) acrylate) are more preferred. The content of the structural unit derived from the carboxyl group-containing monomer is preferably 0.1% to 15% by weight, more preferably 0.5% to 10% by weight, relative to the total structural units constituting the acrylic polymer. In addition, the content of the structural unit derived from the hydroxyl group-containing monomer is preferably 0.1% to 20% by weight, more preferably 0.5% to 10% by weight, and particularly preferably 1% to 7% by weight, relative to the total structural units constituting the acrylic polymer. It should be noted that in this specification, (meth)acrylic acid refers to acrylic acid and / or methacrylic acid. ; In one embodiment, the glass transition temperature Tg of the above-mentioned other monomers is 100°C to 175°C. The content ratio of the structural unit derived from the monomer (also referred to as comonomer (B1)) having a glass transition temperature Tg of 100°C to 175°C is 40 parts by weight or less relative to 100 parts by weight of the base polymer, more preferably 35 parts by weight or less, and further preferably 30 parts by weight or less. If it is such a range, an adhesive sheet that is not easy to break during expansion can be obtained. The content ratio of the structural unit derived from the comonomer (B1) is preferably 5 parts by weight or more relative to 100 parts by weight of the base polymer. If it is such a range, an adhesive sheet with excellent stress transfer can be obtained. The resin layer may be formed from a resin layer-forming composition comprising the base polymer. The resin layer-forming composition may contain any appropriate additive as required. Examples of the additive include: a crosslinking agent, a tackifier, a plasticizer (e.g., a trimellitic acid ester plasticizer, a pyromellitic acid ester plasticizer, etc.), a pigment, a dye, a filler, an anti-aging agent, a conductive material, an antistatic agent, an ultraviolet light absorber, a light stabilizer, a release regulator, a softener, a surfactant, a flame retardant, an antioxidant, etc. Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, and amine crosslinking agents. Among them, an isocyanate crosslinking agent or an epoxy crosslinking agent is preferred. Specific examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; isocyanate adducts such as trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "Coronate HL"), and isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "Coronate HX"); and the like. The content of the isocyanate crosslinking agent is typically 0.1 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, based on 100 parts by weight of the base polymer. Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "Epolight 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "Epolight 1500NP"), ethylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "Epolight 40E"), propylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "Epolight 70P"), polyethylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name "EPIOL E-400”), polypropylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name “EPIOL P-200”), sorbitol polyglycidyl ether (manufactured by Nagase ChemteX, trade name “DENACOL EX-611”), glycerol polyglycidyl ether (manufactured by Nagase ChemteX, trade name “DENACOL EX-314”), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX, trade name “DENACOL EX-512”), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, tris(2-hydroxyethyl)isocyanuric acid triglycidyl ester, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, epoxy resins having two or more epoxy groups in the molecule, and the like. The content of the epoxy crosslinking agent is typically 0.01 to 10 parts by weight, more preferably 0.03 to 5 parts by weight, based on 100 parts by weight of the base polymer. Any appropriate tackifier may be used as the tackifier. For example, a tackifier resin may be used as the tackifier. Specific examples of the tackifier resin include rosin-based tackifier resins (e.g., unmodified rosin, modified rosin, rosin phenolic resins, rosin ester resins, etc.), terpene-based tackifier resins (e.g., terpene resins, terpene phenolic resins, styrene-modified terpene resins, aromatic-modified terpene resins, hydrogenated terpene resins), hydrocarbon-based tackifier resins (e.g., aliphatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aromatic hydrocarbon resins (e.g., styrene resins, xylene resins, etc.), aliphatic-aromatic petroleum resins, aliphatic-alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, coumarone indene resins, etc.), phenolic tackifier resins (e.g., alkylphenolic resins, xylene formaldehyde resins, resol phenolic resins, novolacs, etc.), ketone-based tackifier resins, polyamide-based tackifier resins, epoxy-based tackifier resins, elastic-based tackifier resins, etc. Among them, rosin-based tackifying resins, terpene-based tackifying resins or hydrocarbon-based tackifying resins (styrene-based resins, etc.) are preferred. The tackifier can be used alone or in combination of two or more. The amount of the tackifier added is preferably 5 to 100 parts by weight, more preferably 10 to 50 parts by weight, relative to 100 parts by weight of the base polymer. In one embodiment, the resin layer is not active energy ray-curable. By forming a resin layer that is not active energy ray-curable, it is possible to balance the hardness of the adhesive sheet that is preferred for stress transfer and the elongation at break that can preferably stretch the adhesive sheet. In this specification, "not active energy ray-curable" means that the change in elastic modulus based on the nanoindentation method caused by active energy ray irradiation is 10% or less. The loss modulus E" of the above-mentioned resin layer at -15°C is preferably 10MPa to 3000MPa, more preferably 15MPa to 2500MPa, and further preferably 20MPa to 2400MPa. If it is in such a range, an adhesive sheet with excellent stress transfer properties can be obtained. In particular, in the so-called cold expansion process, an adhesive sheet with excellent stress transfer properties, preferably embodying expandability, can be obtained. In addition, when the loss modulus E" at -15°C is too low, the deformation during heating (for example, heating by laser irradiation) is large, which may cause positional displacement of the adherend. In addition, when the loss modulus E" at -15°C is too high, it may be easy to break during the expansion process. The loss modulus E" can be measured using a dynamic viscoelasticity measuring device (for example, the trade name "RSA-G2" manufactured by TAinstruments) under measuring conditions of a frequency of 1 Hz and a heating rate of 5°C / min. The storage modulus E' of the above-mentioned resin layer at -15°C is preferably 10MPa to 2500MPa, and more preferably 15MPa to 1500MPa. If it is in such a range, an adhesive sheet with excellent stress transfer properties can be obtained. In particular, in the so-called cold expansion process, an adhesive sheet with excellent stress transfer properties and preferably embodying expansion properties can be obtained. In addition, when the storage modulus E' at -15°C is too low, the deformation during heating (for example, heating by laser irradiation) is large, which may cause the position of the adherend to shift. In addition, when the storage modulus E' at -15°C is too high, it may be easy to break during the expansion process. The storage modulus E' can be measured using a dynamic viscoelasticity measuring device (for example, the trade name "RSA-G2" manufactured by TA instruments) under the measuring conditions of a frequency of 1Hz and a heating rate of 5°C / min. The indentation hardness of the above-mentioned resin layer at -10°C based on the nanoindentation method is preferably 0.05 to 15 MPa, more preferably 0.10 to 15.0 MPa, and further preferably 0.10 to 12.0 MPa. If it is in such a range, an adhesive sheet with excellent stress transfer can be obtained. The indentation hardness based on the nanoindentation method refers to the hardness obtained by continuously measuring the load and indentation depth of the indenter when the indenter is pressed into the sample from the time of loading to the time of unloading, and the load load-indentation depth curve obtained. In this specification, the indentation hardness based on the nanoindentation method refers to the hardness measured by a single indentation method at a specified temperature (-10°C) using a nanoindenter (for example, Triboindenter TI-950 manufactured by Hysitron Inc.), using an indenter: Berkovich (triangular pyramid), an indentation speed of 300nm / sec, a withdrawal speed of 300nm / sec, and an indentation depth of 1300nm. The resin layer preferably has a lower indentation hardness at -10° C. than the substrate by nanoindentation. If such a resin layer is formed, a pressure-sensitive adhesive sheet useful as a temporary fixing member in an expansion step that is not easily broken can be obtained. The thickness of the resin layer is preferably 5 to 40 μm, more preferably 5 to 35 μm, further preferably 10 to 30 μm, and particularly preferably 10 to 20 μm. Within such a range, a PSA sheet having excellent stress transfer properties and being less likely to break during expansion can be obtained. C. Adhesive layer The adhesive layer contains heat-expandable microspheres as described above. The adhesive layer may also contain an adhesive. In addition, in one embodiment, the adhesive layer has a light-to-heat conversion capability. The adhesive layer with light-to-heat conversion capability can, for example, absorb a laser of a specified wavelength and generate heat. By the heat generation, expansion / foaming of the heat-expandable microspheres can occur. If the peelability is embodied by a laser, the tiny adherend can be selectively peeled off. Such an effect is particularly significant when combined with an adhesive layer that can form excellent smoothness. As a laser, an IR laser, a UV laser, etc. are used. Preferably, an IR laser is used. The arithmetic surface roughness Ra of the adhesive layer before the heat-expandable microsphere expands (i.e. before heating) is preferably below 500nm, more preferably below 400nm, further preferably below 300nm. If such scope, then can obtain the adhesive sheet to the excellent adhesion of adherend. In addition, can obtain the adhesive sheet that can be pasted with adherend position accuracy well. The thickness of the adhesive layer is preferably 5 to 40 μm, more preferably 7 to 35 μm, and further preferably 20 to 35 μm. Within such a range, an adhesive sheet having excellent smoothness, high adhesion, and excellent stress transfer properties can be obtained despite containing heat-expandable microspheres. The pressure-sensitive adhesive layer preferably has an indentation hardness of less than 100 MPa, more preferably 0.1 MPa to 50 MPa, and even more preferably 0.1 MPa to 10 MPa at 25° C. A pressure-sensitive adhesive sheet having appropriate adhesiveness and expandability can be obtained within such a range. The light absorptivity of the above-mentioned adhesive layer at a wavelength of 900nm is preferably 25% to 100%, more preferably 30% to 95%, and further preferably 40% to 95%. If it is within such a range, an adhesive layer having a light-to-heat conversion capability can be formed and preferably generates heat by irradiation with IR laser, and an adhesive layer having excellent peelability based on heat-expandable microspheres can be formed. (Adhesive) As the adhesive constituting the adhesive layer, there can be listed: acrylic adhesive, rubber adhesive, silicone adhesive, etc. Among them, acrylic adhesive can be preferably used. In addition, as an adhesive, an active energy ray-curable acrylic adhesive (hereinafter referred to as active energy ray-curable adhesive) can also be used. The details of the adhesive are described in, for example, Japanese Patent Publication No. 2015-168711. The description of the publication is cited in this specification as a reference. In one embodiment, an acrylic adhesive is used as the adhesive. Examples of the acrylic adhesive include acrylic adhesives having an acrylic polymer (homopolymer or copolymer) obtained by using one or more (meth) alkyl esters as monomer components as a base polymer. The base polymer may be the polymer described in the above item B. The acrylic adhesive may contain any appropriate additives as required. Examples of the additives include: crosslinking agents, tackifiers, plasticizers (e.g., trimellitic acid ester plasticizers, pyromellitic acid ester plasticizers, etc.), pigments, dyes, fillers, anti-aging agents, conductive materials, antistatic agents, ultraviolet light absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, etc. As the crosslinking agent contained in the acrylic adhesive, for example, isocyanate crosslinking agent, epoxy crosslinking agent, melamine crosslinking agent, peroxide crosslinking agent, urea crosslinking agent, metal alkoxide crosslinking agent, metal chelate crosslinking agent, metal salt crosslinking agent, carbodiimide crosslinking agent, oxazoline crosslinking agent, aziridine crosslinking agent, amine crosslinking agent, etc. can be listed. Among them, isocyanate crosslinking agent or epoxy crosslinking agent is preferred. As the above-mentioned isocyanate crosslinking agent contained in the above-mentioned acrylic adhesive, for example, the crosslinking agent listed in item B can be used. The content of the isocyanate crosslinking agent can be set to any appropriate amount according to the desired adhesive force, and is representatively 0.1 to 20 parts by weight relative to 100 parts by weight of the base polymer, and more preferably 0.5 to 10 parts by weight. As the above-mentioned epoxy crosslinking agent contained in the above-mentioned acrylic adhesive, for example, the crosslinking agent listed in item B can be used. The content of the epoxy crosslinking agent can be set to any appropriate amount depending on the desired adhesive strength, and is typically 0.01 to 10 parts by weight, more preferably 0.03 to 5 parts by weight, based on 100 parts by weight of the base polymer. As the tackifier contained in the acrylic adhesive, any appropriate tackifier can be used. As the tackifier, for example, a tackifier resin can be used. As specific examples of the tackifier resin, the tackifier resins listed in the above item B can be used. The amount of the tackifier added is preferably 5 to 100 parts by weight, more preferably 10 to 50 parts by weight, relative to 100 parts by weight of the base polymer. (Heat-expandable microspheres) As above-mentioned heat-expandable microsphere, as long as can expand or foam the microsphere by heating, just can use any suitable heat-expandable microsphere.As above-mentioned heat-expandable microsphere, for example can use the microsphere that will be easily expanded by heating and be encapsulated in the shell with elasticity.Such heat-expandable microsphere can be made by any suitable method such as cohesion method, interfacial polymerization method etc. Examples of substances that easily expand by heating include low-boiling-point liquids such as propane, propylene, butene, n-butane, isobutane, isopentane, neopentane, n-pentane, n-hexane, isohexane, heptane, octane, petroleum ether, methane halides, and tetraalkylsilane; azodicarbonamide that vaporizes by thermal decomposition; and the like. As the material constituting the above shell, for example, there can be mentioned polymers composed of the following monomers: nitrile monomers such as acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethoxyacrylonitrile, and fumaric acid nitrile; carboxylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and citraconic acid; vinylidene chloride; vinyl acetate; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and β-carboxyethyl acrylate; styrene monomers such as styrene, α-methylstyrene, and chlorostyrene; amide monomers such as acrylamide, substituted acrylamide, methacrylamide, and substituted methacrylamide; etc. The polymer composed of these monomers may be a homopolymer or a copolymer. Examples of the copolymer include vinylidene chloride-methyl methacrylate-acrylonitrile copolymers, methyl methacrylate-acrylonitrile-methacrylonitrile copolymers, methyl methacrylate-acrylonitrile copolymers, and acrylonitrile-methaconic acid copolymers. As the heat-expandable microspheres, an inorganic foaming agent or an organic foaming agent may be used. Examples of the inorganic foaming agent include ammonium carbonate, ammonium bicarbonate, sodium bicarbonate, ammonium nitrite, sodium borohydride, and various azides. In addition, examples of organic foaming agents include: fluorochloroalkane compounds such as trichloromonofluoromethane and dichloromonofluoromethane; azo compounds such as azobisisobutyronitrile, azodicarbonamide, and barium azodicarboxylate; hydrazine compounds such as p-toluenesulfonylhydrazine, diphenylsulfone-3,3'-disulfonylhydrazine, 4,4'-oxybis(benzenesulfonylhydrazine), and allylbis(sulfonylhydrazine); semicarbazide compounds such as p-toluenesulfonylsemicarbazide and 4,4'-oxybis(benzenesulfonylsemicarbazide); triazole compounds such as 5-morpholino-1,2,3,4-thiatriazole; N-nitroso compounds such as N,N'-dinitrosopentamethylenetetramine and N,N'-dimethyl-N,N'-dinitrosoterephthalamide; and the like. The particle size of the heat-expandable microspheres before heating is preferably 0.5 μm to 80 μm, more preferably 5 μm to 45 μm, further preferably 10 μm to 20 μm, and particularly preferably 10 μm to 15 μm. Thus, if the particle size of the heat-expandable microspheres before heating is measured in average particle size, then it is preferably 6 μm to 45 μm, more preferably 15 μm to 35 μm. The above-mentioned particle size and average particle size are values ​​obtained by the particle size distribution determination method in the laser scattering method. The heat-expandable microspheres preferably have a moderate strength that does not break until the volume expansion rate is preferably 5 times or more, more preferably 7 times or more, and further preferably 10 times or more. When using such heat-expandable microspheres, the adhesive force can be efficiently reduced by heat treatment. The foaming start temperature of the above-mentioned heat-expandable microsphere is preferably 80°C to 250°C, more preferably 80°C to 230°C, further preferably 80°C to 200°C, further preferably 80°C to 150°C, particularly preferably 80°C to 120°C, and most preferably 80°C to 100°C. In this specification, the foaming start temperature of the heat-expandable microsphere refers to the minimum temperature at which the thickness of the adhesive layer (the total thickness of the primer layer and the thickness of the adhesive layer in the case of configuring the primer layer) thickens by more than 5% from normal temperature. For example, the foaming start temperature can be equivalent to the temperature at which the adhesive force of the adhesive tape becomes less than 1.0N / 20mm and becomes less than 50% of the initial adhesive force. The content ratio of the heat-expandable microspheres in the above-mentioned adhesive layer can be appropriately set according to the reduction of the desired adhesive force, etc. The content ratio of the heat-expandable microspheres is, for example, 1 to 150 parts by weight relative to 100 parts by weight of the base polymer forming the adhesive layer, preferably 10 to 130 parts by weight, and more preferably 25 to 100 parts by weight. The above-mentioned heat-expandable microsphere can be manufactured by any appropriate method. In one embodiment, the above-mentioned heat-expandable microsphere is obtained by suspension polymerization. Suspension polymerization is usually carried out as described below: monomer (shell forming material) and organic solvent are dispersed in the aqueous dispersion medium containing dispersant, and monomer polymerization is made in the presence of organic solvent. In addition, the dispersion stabilizer that makes dispersion stability can also be utilized. As the dispersion stabilizer in the aqueous dispersion medium, for example, inorganic particles such as silicon dioxide, magnesium hydroxide, calcium phosphate, magnesium hydroxide, etc. can be listed. In addition, as a dispersion stabilization auxiliary agent, for example, the condensation product of diethanolamine and aliphatic dicarboxylic acid, polyvinyl pyrrolidone, methylcellulose, polyethylene oxide, polyvinyl alcohol, various emulsifiers, etc. can be used. By the polymerization condition of above-mentioned suspension polymerization, the kind / addition of mixed components etc., can control the characteristics of heat-expandable microspheres such as the content of particle diameter, organic solvent.For example, by reducing the addition of dispersion agent, the stirring speed when slowing down polymerization, can obtain the heat-expandable microsphere of large particle diameter.In addition, if increasing the coordination amount of monomer or the stirring speed when slowing down polymerization, then can obtain the thick heat-expandable microsphere of shell thickness. (IR absorber) In one embodiment, the adhesive layer includes an IR absorber. The adhesive layer including the IR absorber can exhibit peelability by IR laser irradiation. As the IR absorber, for example, carbon black, cesium tungsten oxide, lanthanum hexaboride, tin-doped indium oxide, antimony-doped tin oxide, anthocyanin compounds, phthalocyanine compounds, dithiol metal complexes, naphthoquinone compounds, diimide compounds, azo compounds, etc. are used. As the resin constituting the resin film, for example, polyimide resins, polyethylene terephthalate resins, polyamide resins, polyetheretherketone resins, polyethylene naphthalate resins, acrylic resins, epoxy resins, etc. Among them, carbon black is preferred. The content of the IR absorber is preferably 0.1 to 30 parts by weight, more preferably 0.3 to 25 parts by weight, based on 100 parts by weight of the base polymer. D. Base material The above-mentioned substrate can be composed of any appropriate material. For example, the substrate can use various sheet-like objects such as plastic film, plastic sheet, paper, cloth, non-woven fabric, metal foil, or their plastic laminates, and plastic laminates. Among them, from the perspective of operability and cost, plastic film and plastic sheet (hereinafter referred to as plastic film) are most preferred. As the raw material of the plastic film, it can be selected as needed from the perspectives of strength, heat resistance, etc. For example, olefin resins with α-olefin as a monomer component such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA); polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); polyvinyl chloride (PVC); polyphenylene sulfide (PPS); amide resins such as polyamide (nylon) and wholly aromatic polyamide (aramid); polyetheretherketone (PEEK), polyimide, polyetherimide, polystyrene, acrylic resin, etc. These raw materials can be used alone or in combination of two or more. In addition, as the plastic film, any of unstretched film, uniaxially oriented film, and biaxially oriented film can also be used. In addition, these films can also be laminated films composed of two or more film layers. From the viewpoint of operability, films to which lubricants such as inert particles are added can also be appropriately used. In one embodiment, the substrate comprises a polyolefin resin, preferably a polypropylene resin. By using a substrate formed of a polyolefin resin, a PSA sheet having excellent expandability and useful as a temporary fixing material in an expansion step can be obtained. In one embodiment, a substrate having the following structure is used: a multilayer structure (e.g., a three-layer structure) including a layer formed of a polyolefin resin (preferably polypropylene) layer and a layer formed of an ethylene-vinyl acetate copolymer resin. By using such a substrate, an adhesive sheet with excellent expandability and useful as a temporary fixture in an expansion process can be obtained. In addition, by adopting a multilayer structure and separating the functions of each layer, it is easy to achieve both expandability and heat resistance when thermal foaming occurs. The thickness of the substrate is preferably 200 μm or less, more preferably 1 μm to 200 μm, further preferably 5 μm to 200 μm, particularly preferably 10 μm to 200 μm, particularly preferably 20 μm to 200 μm, and most preferably 30 μm to 200 μm. If it is such a range, the effect of the present invention is remarkable. In addition, a substrate having excellent strength, softness, flexibility, buckling resistance, etc. can be obtained. The elastic modulus of the substrate at 25°C based on the nanoindentation method is preferably 500MPa to 5000MPa, more preferably 500MPa to 4000MPa, and further preferably 700MPa to 4000MPa. In this specification, the elastic modulus based on the nanoindentation method refers to the elastic modulus measured by a single indentation method at a predetermined temperature (25°C) using a nanoindenter (e.g., Triboindenter TI-950 manufactured by Hysitron Inc.) under the measurement conditions of an indentation speed of about 500nm / sec, a withdrawal speed of about 500nm / sec, and an indentation depth of about 3000nm. The breaking strength of the substrate at -15°C is preferably 15N / 10mm to 45N / 10mm, more preferably 20N / 10mm to 40N / 10mm. If it is in such a range, an adhesive sheet that is not easy to break and is useful as a temporary fixture in the expansion process can be obtained. The breaking strength can be measured using a tensile tester (for example, SHIMADZU, AUTOGRAPH Thermostatic Chambar, AUTOGRAPH AG-I), under the conditions of sample size: 10mm×150mm, distance between chucks: 50mm, after keeping the sample in a chamber at -15°C for 30 minutes, at a tensile speed of 300mm / min. The substrate may be subjected to a surface treatment, such as corona treatment, chromic acid treatment, ozone exposure, flame exposure, high voltage electric shock exposure, ionizing radiation treatment, and primer coating treatment. E. Method for producing adhesive sheet The above-mentioned adhesive sheet can be manufactured by any appropriate method. As the manufacturing method of the adhesive sheet, for example, there can be listed: directly applying a resin layer forming composition on a substrate to form a resin layer, applying an adhesive layer forming composition (adhesive + heat-expandable microspheres) on the resin layer; or a method of transferring a coating layer formed by applying an adhesive layer forming composition on any appropriate substrate to a substrate / resin layer laminate, etc. As the coating method of each of the above-mentioned compositions, for example, a coating method using a die coater, a comma coater, a gravure coater, etc. can be cited. As the drying method, heating drying is preferably adopted. For example, drying can be carried out in the following manner: in a drying machine with an air supply device that can force convection of air set to a specified temperature, the adhesive coating layer is set for an arbitrary time. The drying temperature is preferably 55° C. or higher and less than 100° C., more preferably 60° C. to 90° C., and even more preferably 65° C. to 90° C. The drying time may be any appropriate time. The drying time is, for example, 1 minute to 10 minutes. Within this range, an adhesive layer can be efficiently formed. F. Application The adhesive sheet can be preferably used as a temporary fixing sheet when processing any appropriate member (for example, electronic components such as semiconductor chips). In one embodiment, a dicing die bonding film is provided in which the adhesive sheet and a die attach film are laminated. Figure 2 This is a schematic cross-sectional view of a dicing-die bonding film according to an embodiment of the present invention. The dicing-die bonding film 200 includes an adhesive sheet 100 and a die bonding film 40 disposed on one side of the adhesive sheet 100. The die bonding film is an adhesive film that is attached to a semiconductor chip before die bonding when manufacturing a semiconductor chip, and is attached to a chip in a wafer state so that it can be separated into individual chips together with the wafer during dicing. As a chip bonding film, a chip bonding film known in the technical field can be used, so a detailed description of its composition is omitted. The chip bonding film can function as an adhesive showing curability (e.g., thermosetting), for example. The chip bonding film can contain any appropriate thermosetting resin. As a thermosetting resin, for example, epoxy resin, phenolic resin, amino resin, unsaturated polyester resin, polyurethane resin, silicone resin, and thermosetting polyimide resin can be listed. In the chip bonding film, a thermoplastic resin can also be used in combination. As a thermoplastic resin, for example, natural rubber, butyl rubber, isoprene rubber, chloroprene rubber, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, polybutadiene resin, polycarbonate resin, thermoplastic polyimide resin, 6-nylon, 6,6-nylon and other polyamide resins, phenoxy resins, acrylic resins, saturated polyester resins such as PET and PBT, polyamideimide resins, fluororesins, etc. can be listed. Example Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. In the examples, "parts" and "%" are by weight unless otherwise specified. [Production Example 1] Production of Base Polymer A 70 parts by weight of methyl acrylate (MA), 30 parts by weight of 2-ethylhexyl acrylate (2EHA) and 10 parts by weight of acrylic acid (AA) were added to ethyl acetate, and 0.4 parts by weight of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: PERBUTYL O (registered trademark)) as a polymerization initiator was further added, and the mixture was stirred at 80 to 90° C. for 12 hours to obtain an ethyl acetate solution of polymer A having a solid content concentration of 40% (glass transition temperature Tg: −13° C.). [Production Example 2] Production of Base Polymer B 70 parts by weight of ethyl acrylate (EA), 30 parts by weight of 2-ethylhexyl acrylate (2EHA), 10 parts by weight of N-phenylmaleimide (PMI) and 4 parts by weight of 2-hydroxyethyl acrylate (HEA) were added to toluene, and 0.2 parts by weight of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: PERBUTYL O (registered trademark)) as a polymerization initiator was further added, and the mixture was stirred at 80 to 90° C. for 12 hours to obtain a toluene solution of polymer B having a solid content concentration of 40% (glass transition temperature Tg: −14° C.). [Production Example 3] Production of Base Polymer C 70 parts by weight of ethyl acrylate (EA), 30 parts by weight of 2-ethylhexyl acrylate (2EHA), 5 parts by weight of methyl methacrylate (MMA) and 4 parts by weight of 2-hydroxyethyl acrylate (HEA) were added to ethyl acetate, and 0.4 parts by weight of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: PERBUTYL O (registered trademark)) as a polymerization initiator was further added, and the mixture was stirred at 80 to 90° C. for 12 hours to obtain an ethyl acetate solution of polymer C having a solid content concentration of 40% (glass transition temperature Tg: −32.5° C.). [Production Example 4] Production of Base Polymer D 100 parts by weight of 2-ethylhexyl acrylate (2EHA), 25.5 parts by weight of acryloyl morpholine (ACMO) and 18.5 parts by weight of 2-hydroxyethyl acrylate (HEA) were added to toluene, and 0.2 parts by weight of azobisisobutyronitrile (AIBN) as a thermal polymerization initiator was further used. The concentration of all monomers was adjusted to 60% by weight. A polymerization reaction treatment was carried out at 62°C for 6 hours in a nitrogen gas stream, and a polymerization reaction treatment was further carried out at 75°C for 2 hours to obtain an intermediate of an acrylic copolymer. Next, 22.5 parts by weight of 2-methacryloyloxyethyl isocyanate (MOI) was added to the liquid containing the intermediate of the obtained acrylic copolymer, and dibutyltin dilaurate was added as a reaction catalyst at 0.03% by weight relative to MOI. Then, an addition reaction treatment (urethanization reaction) was carried out at 50°C for 12 hours in an air stream to obtain a toluene solution of polymer D (glass transition temperature Tg: -6°C). [Production Example 5] Production of Base Polymer E 64 parts by weight of butyl acrylate (BA), 33 parts by weight of methyl methacrylate (MMA) and 3 parts by weight of 2-hydroxyethyl acrylate (HEA) were added to ethyl acetate, and 0.2 parts by weight of azobisisobutyronitrile as a polymerization initiator was further added. The mixture was stirred at 80 to 90° C. for 12 hours to obtain an ethyl acetate solution of polymer E (glass transition temperature Tg: −18° C.) having a solid content concentration of 40%. [Production Example 6] Production of Base Polymer F 100 parts by weight of 2-ethylhexyl acrylate (2EHA) and 20.0 parts by weight of 2-hydroxyethyl acrylate (HEA) were added to toluene, and 0.2 parts by weight of azobisisobutyronitrile (AIBN) was further used as a thermal polymerization initiator. The concentration of all monomers was adjusted to 60% by weight. A polymerization reaction treatment was carried out at 62°C for 6 hours in a nitrogen gas stream, and a polymerization reaction treatment was further carried out at 75°C for 2 hours to obtain an intermediate of an acrylic copolymer. Next, 16.0 parts by weight of 2-methacryloyloxyethyl isocyanate (MOI) was added to the liquid containing the intermediate of the obtained acrylic copolymer, and dibutyltin dilaurate was added as a reaction catalyst at 0.03% by weight relative to MOI. Then, an addition reaction treatment (urethanization reaction) was carried out at 50°C in an air stream for 12 hours to obtain a toluene solution of polymer F (glass transition temperature Tg: -53°C). [Manufacturing Example 7] Manufacture of substrate A A two-layer substrate was obtained by co-extrusion molding using an extrusion T-die molding machine. The extrusion temperature was set to 190°C. The thickness and resin composition of each layer are as follows. Layer thickness: Layer 1 containing PP: 80 μm, Layer 2 containing PP: 16 μm. PP-containing layer 1: melting point: 124°C, tensile modulus (90°C): 24.7 [MPa]. Main ingredients: Polypropylene resin 1. Other ingredients: polymer antistatic agent. PP-containing layer 2: melting point: 92°C, tensile modulus (90°C): 1.92 [MPa]. Main component: polypropylene resin 1 (70 parts by weight). Other ingredients: ethylene vinyl acetate copolymer (EVA1) (30 parts by weight). EVA1; melting point: 88°C, tensile modulus (90°C): 1.01 [MPa]. [Example 1] (Production of resin layer / substrate laminate) A mixed solution A was prepared by mixing an ethyl acetate solution of polymer A (polymer A: 100 parts by weight), 1.5 parts by weight of an isocyanate crosslinking agent (trade name "TAKENATE D-101A" manufactured by Mitsui Chemicals, Inc.), and 0.05 parts by weight of dioctyltin dilaurate. The mixed solution A was applied to one surface of the substrate A using a coater to a thickness of 5 μm after solvent volatilization (drying). The solvent was then volatilized (dried) at 70° C. for 1 minute using a forced convection hot air drying oven to obtain a resin layer / substrate laminate. (Production of MRF38 (liner) / adhesive layer (containing heat-expandable microspheres) laminate) A toluene solution of polymer F (polymer F: 100 parts by weight), 1.5 parts by weight of an isocyanate crosslinking agent (manufactured by Mitsui Chemicals, trade name "TAKENATE D-101A"), 30 parts by weight of heat-expandable microspheres (manufactured by Matsumoto Oil & Fats Pharmaceutical Co., Ltd., trade name "FN-100S", foaming start temperature: 125°C, average particle size: 15 μm), and 0.4 parts by weight of a carbon black dispersion (manufactured by Mikoku Color Co., Ltd., trade name "MHI BLACK#PD-837M") were mixed to prepare an adhesive (mixed solution F). The adhesive (mixed solution B) was applied to the release agent coating surface of a liner (PET film, manufactured by Mitsubishi Resins Co., Ltd., trade name "MRF-38") coated with a silicone release agent in such a manner that the thickness after solvent evaporation (drying) became 30 μm. Then, a forced convection hot air drying oven was used to evaporate the solvent (dry) at 65°C for 5 minutes to obtain an MRF38 (liner) / adhesive layer (containing heat-expandable microspheres) laminate. (Production of MRF38 (liner) / adhesive layer (containing heat-expandable microspheres) / resin layer / substrate laminate) The MRF38 (pad) / adhesive layer (containing heat-expandable microspheres) and resin layer / substrate laminate were bonded together in a manner such that the adhesive layer (containing heat-expandable microspheres) and the resin were placed opposite each other, thereby obtaining an adhesive sheet consisting of the MRF38 (pad) / adhesive layer (containing heat-expandable microspheres) / resin layer / substrate laminate. [Examples 2 to 8, Comparative Example 1] When forming the PSA layer, a PSA sheet with a backing was obtained in the same manner as in Example 1 except that the base polymer shown in Table 1 was used and the amount of carbon black dispersion added and the thickness of each layer were set as shown in Table 1. [Comparative Example 2] A toluene solution of polymer F (polymer F: 100 parts by weight), 1.5 parts by weight of an isocyanate crosslinking agent (manufactured by Mitsui Chemicals, trade name "TAKENATE D-101A"), 30 parts by weight of heat-expandable microspheres (manufactured by Matsumoto Oil & Fats Pharmaceutical Co., Ltd., trade name "FN-100S", foaming start temperature: 125°C, average particle size: 15 μm), and 0.4 parts by weight of a carbon black dispersion (manufactured by Mikoku Color Co., Ltd., trade name "MHI BLACK#PD-837M") were mixed to prepare an adhesive (mixed solution F). The adhesive (mixed solution F) was applied to one surface of substrate A to a thickness of 30 μm after solvent volatilization (drying). The solvent was then volatilized (dried) at 65° C. for 5 minutes using a forced convection hot air drying oven to obtain an adhesive sheet (adhesive layer / substrate). <Evaluation> After the liner was peeled off from the PSA sheets with liner obtained in Examples and Comparative Examples, the PSA sheets were subjected to the following evaluations. (1) Laser peeling The die bonding film and the semiconductor chip were sequentially arranged on the adhesive layer of the adhesive sheet, and IR laser (wavelength: 940 nm) was irradiated from the substrate side of the adhesive sheet to evaluate the peelability of the adherend (die bonding film / semiconductor chip laminate) from the adhesive layer. After IR laser irradiation, the case where the adherend peeled naturally was rated as qualified (O), and the case where it did not peel naturally was rated as unqualified (×). Evaluation equipment: L13920-611, laser irradiation diameter 6.4 mmφ (manufactured by Hamamatsu Photonics). A11612-K8DD5AR, laser transmission fiber (manufactured by Hamamatsu Photonics). A15558-55-80DW, laser irradiation unit, 6.4 mmφ (manufactured by Hamamatsu Photonics). Evaluation conditions: output power 50W. Irradiation time: 50msec. (2) Die Attach Film (DAF) cutting properties A die attach film and a semiconductor wafer were placed on the adhesive layer of the adhesive sheet in this order (stealth dicing was completed), and dicing was attempted under the following conditions. A dicing rate of 90% or more was considered acceptable, and a dicing rate of less than 90% or a film break was considered unacceptable. Evaluation equipment: DDS (manufactured by DISCO Corporation). Die Attach Film. Chip size: 4mm×13mm×30μmt. Chip material: Silicon. Evaluation conditions: Ambient temperature 0°C. Cold expansion ejection height 10mm. Cold expansion ejection speed 200mm / sec. Heat shrink ejection height. Heat shrinkage hot air temperature is 250℃. The heat shrinking rotation speed is 5° / sec. (3)DAF adhesion [Production of Die Attach Film (DAF)] · Acrylic polymer (product name "SG-P3", manufactured by Nagase ChemteX Co., Ltd., glass transition temperature 12° C., containing epoxy groups) 35 parts by mass (solid content). · Acrylic polymer (acrylic resin solution obtained by dissolving a copolymer of ethyl acrylate, butyl methacrylate and glycidyl methacrylate in methyl ethyl ketone: weight average molecular weight Mw = 70,000 / epoxy equivalent = 444 (g / eq) / glass transition temperature Tg = 11°C) 30 parts by mass (solid content). · Phenolic resin (product name: "MEHC-7851SS", manufactured by Meiwa Chemicals Co., Ltd.) 6 parts by mass Silica filler (product name: "SE2050-MCV", manufactured by Admatechs) 27 parts by mass Silane coupling agent (product name: "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) 2 parts by mass The above-mentioned raw materials were added to a predetermined amount of methyl ethyl ketone and mixed to prepare an adhesive composition solution having a total solid content concentration of 15% by mass. Next, using the prepared adhesive composition, a die bonding film having a thickness of 10 μm was produced on a PET release liner in the same manner as above. The chip bonding film prepared in the above is laminated with the adhesive sheet obtained in the embodiment or comparative example to obtain a laminate, and a strong adhesive tape (made by Nitto Denko Corporation, NO.315) is attached to the chip bonding film surface of the laminate, and a size of 100 mm in width and 200 mm in length is cut. A tensile testing machine (made by SHIMADZU, AUTOGRAPH AGX-V) was used in the measurement. The substrate and the adhesive layer were clamped with an upper chuck fixture, and a peeling test was performed at a speed of 100 mm / min and T-type peeling to measure the DAF adhesion. The measurement was carried out at a temperature of 23°C. (4) Storage modulus E' at -15°C The storage modulus E' and loss modulus E" of the resin layer and the storage modulus E' of the PSA sheet were measured using a dynamic viscoelasticity measuring apparatus (trade name "RSA-G2" manufactured by TA Instruments) under the measurement conditions of frequency 1 Hz, heating rate 5°C / min, and measurement temperature -15°C. (5) Indentation hardness at -10°C The indentation hardness of the resin layer at -10°C was measured using a nanoindenter (Triboindenter TI-950 manufactured by Hysitron Inc.) by a single indentation method at -10°C, using an indenter: Berkovich (triangular pyramid), an indentation speed of 300 nm / sec, a withdrawal speed of 300 nm / sec, and an indentation depth of 1300 nm. (6) IR absorptivity of adhesive layer The IR (wavelength: 900 nm) absorptivity of the adhesive layer was measured using a spectrophotometer model "SOLID SPEC-3700" manufactured by SHIMADZU Co., Ltd. The measurement conditions were a measurement wavelength range of 280 nm to 2500 nm, a scanning speed of medium speed, and a sampling pitch of 1 nm. [Table 1]

Claims

1. An adhesive sheet comprising: a substrate, a resin layer, and an adhesive layer in this order; The adhesive layer contains heat-expandable microspheres, The resin layer comprises a base polymer, The base polymer has a glass transition temperature Tg of -35°C to 20°C.

2. The adhesive sheet according to claim 1, wherein The loss modulus E" of the resin layer at -15°C is 10 MPa to 3000 MPa.

3. The adhesive sheet according to claim 1, wherein The storage modulus E' of the resin layer at -15°C is 10 MPa to 2500 MPa.

4. The adhesive sheet according to claim 1, wherein The resin layer is not active energy ray-curable.

5. The adhesive sheet according to claim 1, wherein The thickness of the resin layer is 5 μm to 40 μm.

6. The adhesive sheet according to claim 1, wherein The base polymer has a structural unit A1 derived from a monomer A1, and the glass transition temperature Tg of the monomer A1 when made into a homopolymer is -20°C to 15°C, The content of the structural unit A1 is 50 parts by weight or more based on 100 parts by weight of the base polymer.

7. The adhesive sheet according to claim 6, wherein The base polymer is an acrylic polymer, Monomer A1 is ethyl acrylate, methyl acrylate or 2-ethylhexyl methacrylate.

8. The adhesive sheet according to claim 1, wherein The base polymer has a structural unit B1 derived from a monomer B1, and the glass transition temperature Tg of the monomer B1 when made into a homopolymer is 100° C. to 175° C., The content of the structural unit B1 is 40 parts by weight or less based on 100 parts by weight of the base polymer.

9. The adhesive sheet according to claim 8, wherein The monomer B1 is methyl methacrylate, N-acryloylmorpholine, N-vinyl-2-pyrrolidone or N-phenylmaleimide.

10. The adhesive sheet according to claim 1, wherein The thickness of the adhesive layer is 5 μm to 40 μm.

11. The adhesive sheet according to claim 1, wherein The light absorptivity of the adhesive layer at a wavelength of 900 nm is 25% to 100%.

12. The adhesive sheet according to claim 1, wherein The substrate includes a polyolefin-based resin.

13. The adhesive sheet according to claim 1, wherein The substrate includes a layer formed of a polyolefin-based resin layer and a layer formed of an ethylene-vinyl acetate copolymer-based resin. 14 . A dicing die bonding film comprising the adhesive sheet according to claim 1 and a die bonding film.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive sheet with separator, assembly of optical member and method for assembling the same

    JP2003201452A

  • Pressure sensitive adhesive sheet

    JP2015168711A